A Comparative Evaluation of the Wettability of Two Denture Base Materials to Artificial Saliva and Distilled Water: An In vitro Study - Athira Kattachirakunnel Sasi; William Thomas; C.V Revathy; Vinaya Murali; V.H Dhanya; Ambili Ravindran (Journal of Nature and Science of Medicine)
Aim: The aim of this in vitro study is to compare the wettability of two denture base materials to salivary substitute and distilled water. Materials and Methods: The present study was conducted to compare the wettability of two denture base materials to saliva substitute and distilled water using contact angle measurement by Contact Angle Goniometer. A total of 56 samples were made (14 of conventional polymethyl methacrylate (PMMA) and 14 of denture base material used in biofunctional prosthetic system [BPS]). The advancing contact angle (ACA) and receding contact angle (RCA) were measured using contact angle goniometer. The angle of hysteresis (difference between ACA and RCA) was also found out. Those with the lowest values of advancing and RCAs had more wettability and those with the highest angle of hysteresis had the greatest retention. The values obtained were subjected to the Kruskal–Wallis test and student’s t-test. Results: When groups 1 and 2 were compared, P value obtained was >0.05 which indicated no significant difference in ACA and RCA. Similar comparisons were made between all groups. Conclusion: Based on the statistical analysis, it could be concluded that denture base material used in BPS system had the greatest wettability and retention when used with artificial saliva when compared with the conventional PMMA resin.